Las Tunas. Escenarios demográficos de la población. 2015-2030. / Las Tunas. Demographic Scenarios of the Population. 2015-2030. - Otilia Barros Díaz; Miguel Fernández Rodríguez; Maribel Fernández Noguel (Universidad de La Habana, 2021)
The objective of the article is to present the results of the demographic scenarios of the population of the province Las Tunas 2015-2030, based on the current situation of demographic variables, fecundity, mortality and migrations. The scenarios presented complement the projections elaborated by the National Statistic Office. The results obtained project a slow population growth that, from the 2015-2020 period could begin to decrease, and an increase in the speed of the aging process. The fundamental factors in the future behavior of the population are located in the level of fertility and in young population's loss as a result of the migratory movement. The attention to the demographic dynamics of the province is a key factor in the development planning and management process for the coming years. / RESUMEN El objetivo del artículo es presentar los resultados de los escenarios demográficos de la población de Las Tunas 2015-2030, tomando como base la situación actual de las variables demográficas, fecundidad, mortalidad y migraciones. Los escenarios presentados complementan las proyecciones elaboradas por la Oficina Nacional de Estadística. Los resultados obtenidos proyectan un lento crecimiento de la población que, a partir del quinquenio 2015-2020, pudiera comenzar a disminuir, y un incremento de la velocidad en el proceso de envejecimiento. Los factores fundamentales en el comportamiento futuro de la población se ubican en el nivel de la fecundidad y en la pérdida de población joven como resultado del movimiento migratorio. La atención a la dinámica demográfica de la provincia resulta un factor clave en el proceso de planificación y gestión del desarrollo para los próximos años.